A metal–organic framework featuring highly sensitive fluorescence sensing for Al3+ ions. Issue 46 (5th November 2021) - Qiao, Yang; Li, Zeqi; Yu, Mei-Hui; Chang, Ze; Bu, Xian-He
Abstract : A new fluorescent MOF can detect Al 3+ ions with high selectivity and sensitivity via turn-off effect and emission color change. Abstract : High sensitivity and selectivity for the detection of metal ions are very important to protect human health. Fluorescent metal–organic frameworks (MOFs) as new sensing materials have attracted more and more attention. Herein, a pillar-layered fluorescent metal–organic framework, {[H2 N(CH3 )2 ]2 [Cd5 (TCPE)3 (4, 4′-bpy)2 (MeOH)2 (H2 O)4 ]} n (NKM-102 ) (H4 TCPE = tetrakis(4-carboxyphenyl)ethylene acids, 4, 4′-bpy = 4, 4′-bipyridine), has been synthesized through utilization of the H4 TCPE ligand with typical AIE characteristics. NKM-102 exhibits excellent fluorescence emission performance and detects Al 3+ ions with high selectivity through turn-off effect and emission color change. Moreover, the detection limit of NKM-102 can reach 158 ppb, which is lower than the maximum limit of Al 3+ ions in drinking water recommended by the United States Environmental Protection Agency (200 ppb). Therefore, the NKM-102 probe is a prominent candidate for the visual detection of Al 3+ ions with high sensitivity and selectivity.